The Future of Learning in the Metaverse: How Virtual Reality is Creating New Educational Opportunities - Cittra Juniarni; Ani Nafisah; Suib Rizal; Awaludin Awaludin; Muhammad Anggung Manumanoso Prasetyo (Education Studies and Teaching Journal (EDUTECH), 2024)
Metaverse, the result of the evolution of augmented reality (AR) and virtual reality (VR) technology, has brought revolutionary changes in education by offering an interactive and immersive digital environment. The aim of this research is to investigate the impact of the Metaverse on the design and experience of virtual learning in an educational context. A systematic literature review approach was used to collect and analyze related articles from international databases such as Scopus, IEEE Xplore, and Google Scholar. The analysis results show that Metaverse allows educators to create more dynamic and interactive learning experiences, with the integration of various design models and pedagogical strategies. The implication of this research is that the use of the Metaverse in education has great potential to improve learning effectiveness, although its implementation requires a careful approach to overcome the associated technical and pedagogical challenges.